Determinants of Islamic Social Responsibility Disclosure the Case of Islamic Bank: Cross Country Analysis - Agus Maulana; Evony Silvino Violita (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2020)
Introduction to The Problem: The rapid growth of Islamic financial institutions around the world attracts a lot of attention, but its growing is not supported by adequate accountability. Several evidence show that accountability of Islamic banks is still very low. The lack of accountability may causes low public trust, so it is important to study the determinant of Islamic Social Responsibility Disclosure by Islamic Bank.Objective Study: This study intends to examine the determinants of Islamic Social Responsibility disclosure (ISR). So practitioners and academics can get a clear view of Islamic Bank's accountability through ISR disclosure.Methodology: This paper applies some theories such as stakeholder theories, agency theory, and legitimacy theory to developed hypotheses linking ISR disclosure and its determinants (internationality, Islamic Corporate Governance, and Socio-Political Context). This paper uses the content analysis method to assess the ISR disclosure of Islamic banks from 13 countries spanning from 2014 to 2016. The ISR index consists of 72 items developed based on AAOIFI. Finally, OLS Regression Analysis is used to test the hypotheses.Findings: The paper find that the level of ISR disclosure is still very low (44%). From the internationality aspect, we found that the proportion of foreign ownership and the status of the multinational corporation influenced the level of ISR disclosure, but we did not find evidence that the CEO's overseas experience affected the level of disclosure. This paper also confirm that Islamic Corporate Governance and Socio-Political context are the main determinant of ISR disclosure by Islamic Bank.